Ten Years Survey of Primary HIV-1 Resistance in Serbia: The Occurrence of Multiclass Resistance - Stanojevic, Maja (Mary Ann Liebert, Inc., 2014)
In Serbia, the first cases of HIV infection were reported in 1985, whereas antiretroviral (ARV) therapy has been in use since 1987. With this study we aimed to assess the occurrence and pattern of HIV resistance mutations among newly diagnosed patients in the period 2002–2011. The study prospectively included 181 adult patients. Genotypic HIV-1 drug resistance testing was performed and drug resistance was scored according to the 2009 WHO list for surveillance of drug resistance mutations (SDRMs). A bioinformatic approach was used to estimate the duration of infection by calculating the percentage of ambiguous basecalls per sequence, with a cutoff of 0.47% as the delimiter for recent infection. The overall prevalence of transmitted drug resistance (TDR) found in the study was 8.8% (16/181, 95% CI=5.5–13.8). Thirty-one percent of resistant samples contained multiple SDRMs. In particular, 5/16 patients with resistance carried viral strains with SDRMs to multiple ARV classes, hence one-third of resistant strains were multiclass resistant, including non-B strains. A total of 51.9% of samples (94/181) were classified as recent infection, with a significant increase in the second part of the study period. However, the prevalence of TDR in recent infection was 6.4% (6/94, 95% CI=2.9–13.2), not statistically different from that found in nonrecent infection. We showed a changing pattern of TDR mutations over the study period, with a substantial occurrence of multiclass resistance, across different HIV subtypes. Our results highlight the need for continued surveillance of primary resistance.